ATTITUDE TOWARDS TRADITIONAL, COMPLEMENTARY AND ALTERNATIVE MEDICINES (T&CAM) AND ITS USE AMONG WOMEN DURING ANTENATAL AND POSTNATAL PERIOD - Basanta Kumar Mohanty; Siti Fatimah binti Muhammad Nor; Andek Noor Faaezah binti Mohd Sadek; Saw Ohn Mar (Asian Journal of Medicine & Health Sciences, 2020)
Aim: This study investigated women’s attitude towards the use of traditional complementary and alternative medicine (T&CAM) during pregnancy and postnatal period and their practices of T&CAM during that period and its association with socio-demographic variables. Methodology: A cross-sectional descriptive study conducted among antenatal and postnatal clinic attenders at MCH clinic of Klinik Kesihatan Manjoi. Data were collected by using structured prevalidated questionnaire. Result: Out of total 103 respondents, 66.02% were antenatal and 33.98% were postnatal women with the mean age of 29.72 years. Prevalence of T&CAM among the participants was 25.24%. T&CAM use was not prevalent among pregnant or breast feeding mothers (p<0.05). There was no significant association of use of T&CAM with sociodemographic variables. The majority (95.15%) of the respondents demonstrated good attitude towards T&CAM use. Dietary method (restraining some food) was the most commonly practiced method. “The rest methods” were used by 30.10% of the respondents, followed by massage and hot stones (24.27%), herbal bath (21.36%), herbal drinks (9.71%) and abdominal wrap (5.83%). Conclusion: The prevalence of T&CAM among our study population is lower than that reported by previous studies. The respondents, irrespective of their sociodemographic back ground, demonstrated good attitude towards the use and they prefer safe practices. There is need to study the details of individual methods to understand more about the rationale of using those specific methods.